2021
DOI: 10.3390/jcm10071349
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative Stress in Acute Myeloid Leukemia Patients after Red Blood Cell Transfusion, but Not Platelet Transfusion, Results Mainly from the Oxidative/Nitrative Protein Damage: An Exploratory Study

Abstract: Chronic oxidative stress (OS) can be an important factor of acute myeloid leukemia (AML) progression; however, there are no data on the extent/consequence of OS after transfusion of packed red blood cells (pRBCs) and platelet concentrates (PCs), which are commonly used in the treatment of leukemia-associated anemia and thrombocytopenia. We aimed to investigate the effects of pRBC/PC transfusion on the OS markers, i.e., thiol and carbonyl (CO) groups, 3-nitrotyrosine (3-NT), thiobarbituric acid reactive substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Third, Khoy et al reported that ROS production upon neutrophil activation plays a role in transfusion-related acute lung injury [ 11 ]. Fourth, Czubak et al reported that oxidative stress increased after RBC transfusion, but not after platelet transfusion [ 12 ]. Above all, this transfusion-related increase in ROS is only observed in macrophages [ 13 ], neutrophils [ 10 , 11 ], and RBCs [ 12 ], but not in platelets, which is consistent with the results of our studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, Khoy et al reported that ROS production upon neutrophil activation plays a role in transfusion-related acute lung injury [ 11 ]. Fourth, Czubak et al reported that oxidative stress increased after RBC transfusion, but not after platelet transfusion [ 12 ]. Above all, this transfusion-related increase in ROS is only observed in macrophages [ 13 ], neutrophils [ 10 , 11 ], and RBCs [ 12 ], but not in platelets, which is consistent with the results of our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, Czubak et al reported that oxidative stress increased after RBC transfusion, but not after platelet transfusion [ 12 ]. Above all, this transfusion-related increase in ROS is only observed in macrophages [ 13 ], neutrophils [ 10 , 11 ], and RBCs [ 12 ], but not in platelets, which is consistent with the results of our studies. According to our results, which show that mixing pRBCs and washed platelets does not increase platelet ROS levels, one can imagine that the administration of antioxidants does not suppress the platelet ROS level that is not increasing, as noted in our results ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid peroxidation. The level of lipid peroxidation in lysates was measured on the basis of the content of peroxidation products reacting with thiobarbituric acid (0.37% TBA) in 0.25 M HCl [26,27]. The lysates were mixed with trichloroacetic acid (20% TCA) in 0.25 M HCl and TBA, and boiled for 15 min.…”
Section: Aaem Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%
“…It may help protect against the development of cancer by boosting immune function [22], [23]. Several studies have found a reduction in vitamin E levels in leukemia patients [23,24]. Tsamesidis et al revealed that increased oxidative stress in the serum of leukemia patients is associated with a decrease in vitamin E concentration, total antioxidant capacity (TAC), and an increase in ROS levels [25].…”
mentioning
confidence: 99%